Background discrimination with a Micromegas detector prototype and veto system for BabyIAXO - Altenmüller, K.; Castel, J. F.; Cebrián, S.; Dafni, T.; Díez-Ibañez, D.; Ezquerro, A.; Ferrer-Ribas, E.; Galan, J.; Galindo, J.; García, J. A.; Giganon, A.; Goblin, C.; et al. (Frontiers in Physics, 2024)
In this paper we present measurements performed with a Micromegas X-ray detector setup. The detector is a prototype in the context of the BabyIAXO helioscope, which is under construction to search for an emission of the hypothetical axion particle from the sun. An important component of such a helioscope is a low background X-ray detector with a high efficiency in the 1-10 keV energy range. The goal of the measurement was to study techniques for background discrimination.In addition to common techniques we used a multi-layer veto system designed to tag cosmicray induced neutron background. Over an effective time of 52 days, a background level of 8.6 × 10 -7 counts keV -1 cm -2 s -1 was reached in a laboratory at above ground level. This is the lowest background level achieved at surface level. In this paper we present the experimental setup, show simulations of the neutron-induced background, and demonstrate the process to identify background signals in the data. Finally, prospects to reach lower background levels down to 10 -7 counts keV -1 cm -2 s -1 are discussed.